Nursing Roles and Outcome of Maternal and Child Health Services in Primary Care Unit of Health Region 11 - Rabiablert, Patinya; Noonil, Naiyana; Petsirasan, Rewwadee (Princess of Naradhiwas University Journal, 2021)
The purpose of this cross-sectional descriptive study was to compare the nursing roles and outcomes of maternal and child health services, according to Key Performance Indicator (KPI), in primary care unit of Health Region 11. The samples were 40 nurses working in primary care unit, selected by purposive sampling technique. The instruments used comprised of 1) a questionnaire asking about nursing roles, 2) an interview form to collect information about problems and obstacles and 3) KPI form for outcome assessment. The instruments received the Content Validity Index (CVI) 0.96, 0.97 and 1.00, respectively. The questionnaire and the KPI form received Cronbach alpha coefficients 0.95 and 0.90. The quantitative data were analyzed using descriptive statistics; frequency, percentage, mean, standard deviation, comparing median by Mann-Whitney test. The qualitative data were analyzed using thematic analysis and categorizing the key points of the data. The results showed that the nurses had about 21 years of nursing experience (SD = 8.9) and had work experiences in the primary care unit approximately 9.1 years (SD =7.7, Med 7.0) Besides, 87.5% of nurses were registered as a nurse practitioner (NP). However, only 15% of the nurses were trained on maternal and child health. The roles of maternal and child health nurses in the primary care unit of a subdistrict’s health promoting hospital and primary care cluster were significantly different (p <.05). Seeing in each aspect, it was found the difference aspects were postpartum care and caring for school-age children and adolescents. The outcomes of other aspects were found at above the standard level except the weight and height of school-aged children. Problems and obstacles in maternal and child services were nurses having a workload, insufficient equipment, and lack of specialized knowledge and skill in maternal and child health which could affect the work performance.